Comparative study of aerobic performance between football and judo groups in prepubertal boys - Triki, M.; Haithem Rebai, H.; Shamssain, M.; Masmoudi, K.; Fellmann, N.; Zouari, H.; Zouari, N. (Asian Journal of Sports Medicine, 2013)
Purpose: The aim of this study was to compare the impact of the practice of football and judo on lung function and aerobic performance of prepubertal boys.